(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The present thesis serves to analyse the effectiveness of the activities pursued by the local government units in question to the benefit of the development of tourism. Effectiveness is one of the forms of the efficiency of the actions evaluated with the respect of reaching the goal that was intended. It constitutes the basis for this evaluation. The area of research covered by the present thesis is one of the seven Polish tourist macro-regions delineated by the Institute of Tourism: the Region of the Baltic Sea Coast and the Pomeranian Lake District (Pomerania). The overriding goal of the thesis is an attempt to make an evaluation of the effectiveness of the activities undertaken by local government units for the development of tourism